2021
DOI: 10.1093/nar/gkab790
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of transcription activation by the global regulator Spx

Abstract: Spx is a global transcriptional regulator in Gram-positive bacteria and has been inferred to efficiently activate transcription upon oxidative stress by engaging RNA polymerase (RNAP) and promoter DNA. However, the precise mechanism by which it interacts with RNAP and promoter DNA to initiate transcription remains obscure. Here, we report the cryo-EM structure of an intact Spx-dependent transcription activation complex (Spx–TAC) from Bacillus subtilis at 4.2 Å resolution. The structure traps Spx in an active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
(92 reference statements)
1
18
3
Order By: Relevance
“…MicF encodes an antisense RNA involved in multidrug resistance by repressing expression of the major membrane porin, OmpF ( 47 , 48 ). The micF DNA scaffold is composed of a 20 bp Rob binding box robbox (including recognition element A site with sequence of GCAC and recognition element B site with sequence of CAAA which overlaps with the –35 element), and a 13 bp non-complementary transcription bubble (–11 to +2) with a consensus –10 element, which was positioned at the catalytic center of RNAP for stabilizing core RNAP and allowing RNA synthesis (Figure 1A ) ( 12 , 16 , 18 , 49 ). Meanwhile, our in vitro Mango-based transcription assay showed that, in the presence of Rob, E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MicF encodes an antisense RNA involved in multidrug resistance by repressing expression of the major membrane porin, OmpF ( 47 , 48 ). The micF DNA scaffold is composed of a 20 bp Rob binding box robbox (including recognition element A site with sequence of GCAC and recognition element B site with sequence of CAAA which overlaps with the –35 element), and a 13 bp non-complementary transcription bubble (–11 to +2) with a consensus –10 element, which was positioned at the catalytic center of RNAP for stabilizing core RNAP and allowing RNA synthesis (Figure 1A ) ( 12 , 16 , 18 , 49 ). Meanwhile, our in vitro Mango-based transcription assay showed that, in the presence of Rob, E .…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid pET28a- rob encoding C-terminal His6 tagged E. coli Rob under the control of T7 promoter was synthesized by Sangon Biotech, Inc. Linear micF _ mango DNA fragment corresponding to –85 to +50 of E. coli micF promoter followed by Mango III coding sequence was generated by de novo PCR using primers of micF _ mango F1, R1 and R2 ( Supplementary Table S1 ) ( 16 , 33–36 ), purified using the QIAquick PCR Purification Kit (Qiagen, Inc.), and stored at –80°C. Two strands of m icF DNA fragment corresponding to –63 to +20 of micF promoter were synthesized and annealed in a mole ratio of 1:1.…”
Section: Methodsmentioning
confidence: 99%
“…Three-dimensional-structure similarity searches of the AlphaFold prediction for full-length CTL0286, performed on the DALI server (90, 91), identified bacterial ω subunits as the three top hits, with Z-scores of 3.8, 3.4, and 3.1, for RNAP ω subunits of Clostridium difficile (99), Mycobacterium tuberculosis (100), and Bacillus subtilis (101), respectively (Table 2). Three-dimensional-structure similarity searches of the AlphaFold prediction for the N-terminal region of CTL0286 (residues 1-62), performed on the DALI server (90, 91), identified bacterial ω subunits as the three top hits, with Z-scores of 5.2, 5.1, and 4.9 for RNAP ω subunits of Escherichia coli (102), Mycobacterium tuberculosis (103), and Bacillus subtilis (104), respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Spx interacts with the C-terminal domain of the α-subunit (αCTD) of the RNA polymerase (RNAP), activating or repressing target genes in order to cope with the stress ( Zuber, 2004 ; Newberry et al, 2005 ; Reyes and Zuber, 2008 ; Lamour et al, 2009 ; Nakano et al, 2010 ; Rochat et al, 2012 ). As revealed by structural studies, redox activated Spx with a disulfide bond between the two cysteine residues (Cys10 and Cys13) interacts both with the αCTD and σ A in the holo RNAP, and this complex binds to the −44 position of promoter DNA to enhance transcription activation ( Shi et al, 2021 ). Among the Spx-induced genes are trxA (thioredoxin) and trxB (thioredoxin reductase), as well as the clpX , clpE , and clpC genes, and putatively clpP ( Nakano et al, 2003 ; Rochat et al, 2012 ).…”
Section: Regulators Of the Proteotoxic Stress Responsementioning
confidence: 99%